Individual Dan Organizational Unlearning: Proposisi Hubungan Moderasi Cross-Level - Henri Dwi Wahyudi (Benefit: Jurnal Manajemen dan Bisnis, 2016)
Unlearning stripped result old learning to give space for new information and new attitude. Unlearning is undoubtedly for individu or organization to receive new knowledge (herdberg,1981), increase innovation performance (pighin Marzona,2011) and increase the company abbility to facing  crisis (Starbuck, 1995), this article give six preposision that connect the literature from micro level and macro level use the mediation variable, multi level moderation to explain the fenomena in organizational behavior that don’t have enough support in empirical, individual and organizational unlearning.